Applicability of CHIRPS Satellite Precipitation in Hydrological Modeling of the Poorly Gauged Himalayan Basin: A Case Study of Sunkoshi Basin, Nepal - Yadav, Bibek Kumar; Regmi, Ram Krishna (International Journal on Engineering Technology and Infrastructure Development, 2026)
This study evaluates the applicability of the CHIRPS Satellite Precipitation Products (SPPs) for runoff simulation in the ungauged Sunkoshi Basin, Nepal. Limited studies have assessed the performance of CHIRPS SPPs in this region, leaving their potential largely underexplored. Given that most of Nepal’s river basins remain ungauged due to extreme terrain and climatic conditions, hydrological modeling plays a crucial role in water resources management. A HEC-HMS model was calibrated (1997-2010) and validated (2014-2018) at the Hampachuwar outlet using observed DHM precipitation and discharge data. Runoff simulations using CHIRPS as input achieved good performance, with NSE score of 0.753 and R2 of 0.771 during calibration, and NSE score of 0.814 and R2 of 0.798 during validation, while PBIAS score of 4.3% and -10.5% for calibration and validation respectively. These results demonstrate that CHIRPS precipitation provides reliable estimates for hydrological modeling, indicating its suitability for application in ungauged or poorly gauged basins of Nepal for improved water resources management and flood risk assessment.